Fabrication and wear performance of (Cu–Sn) solution/TiCx bonded diamond composites - Baoyan, L.; Danhui, H.; Wangxi, Z. (Сверхтвердые материалы, 2018)
The Cu(Sn)–TiCx bonded diamond composites were prepared by in situ reaction sintering of Cu, Ti₂SnC and diamond powders. Effect of Ti₂SnC content on the phase composition, microstructure and grinding properties were studied.